Trends in Positive Urine Culture Rates and Antimicrobial Resistance in Non-Hospitalized Children from Western Romania: A Retrospective Observational Study - Constantin Catalin Marc; Maria Daniela Mot; Monica Licker; Delia Muntean; Daniela Teodora Marti; Ana Alexandra Ardelean; Alina Ciceu; Sergiu Adrian Sprintar; Daniela Adriana Oatis; Alin Gabriel Mihu; Tudor Rares Olariu (Antibiotics, 2025)
Background: Urinary tract infections (UTIs) are among the most common types of infections during childhood. Limited data are available on the prevalence of UTI in children from Romania, with most being available for hospitalized children. For this reason, we conducted a retrospective observational study in consecutive non-hospitalized children to assess the number of positive UTI samples and the antibacterial resistance of causative pathogens. Methods: This study included 7222 consecutive urine cultures collected from children aged 1 to 18 years who are residents of Arad County, Western Romania. Urine samples were analyzed for leukocyturia and cultures for the presence of monomorphic bacteria. Results: The overall number of positive UTI samples was 10.44%. A higher number of positive UTI samples was observed in females when compared to males and in children aged 6–12 and 12 to 18 years when compared to those aged 1–5 years. The antibiotic susceptibility testing of E. coli isolates revealed high sensitivity to most tested antibacterials. Near-complete susceptibility was observed for fosfomycin (99.71%) and nitrofurantoin (96.01%), while high susceptibility rates were also observed for ciprofloxacin (85.43%) and amoxicillin–clavulanic acid (75.05%). In contrast, high resistance was found for ampicillin (62.28% resistant) and trimethoprim–sulfamethoxazole (36.53% resistant). Conclusions: Given the clinical risks associated with UTI in children, our findings underscore the urgent need for the continued monitoring of multidrug-resistant strains. Our study provides important epidemiological and resistance data to guide empirical treatment and strengthen pediatric antimicrobial resistance surveillance. Future studies should focus on different regions and regularly update resistance patterns to keep treatment and prevention strategies aligned with local conditions.